Post Keynesian Money Supply Endogeneity in Malaysia: An Empirical Investigation - Sabri, Nayan (2010)
The stability, progress and the general welfare of an economy would depend much on the level of its money supply as well as the monetary policy initiated by its monetary authority. The central issue is, does the quantity of money supply determine the levels of economic activities and production, or are economic activities and production that actually determine the level of money supply in an economy? According to Post Keynesian analysis, money supply endogeneity are based on four 'subschool' i.e., Horizontalist, Structuralist, Liquidity Preference View and Circuit Theory of Money. This study attempts to investigate empirically the issue of endogeneity/exogeneity of money supply, based on the Malaysian economic environment and planned to meet two major objectives. First, is to identify whether the supply of money in Malaysia is endogenously or exogenously determined. Secondly, if money supply in Malaysia is endogenously determined, the data will be analyzed further to identify the sub-school of Post Keynesian economics that these data supports. The data are analyzed by utilizing the Johansen (1990/91) cointegration procedure, involving three steps; namely, unit root tests, cointegration tests and vector error correction model (VECM) analysis. The empirical findings are summarized into five major points. First, the Malaysia GDP causes money supply (i.e., M1, M2 and M3). Secondly, bank loan causes monetary aggregate (i.e., MO, M1, M2, and M3). The third finding that policy rate or interbank rate (IBR) causes base lending rate (BLR), T-bill rate (TBR) and the Malaysian government securities for five years rate (MGS5R). Followed by the fourth finding, deposits cause reserves. The last major finding of the study involves the relationships between bank loan and money multipliers: the MI money multiplier(MIMPR), the M2 money multiplier (M2MPR) and the M3 money multiplier (M3MPR). The empirical evidence provided in the present thesis is strongly consistent with the hypothesis that money supply in Malaysia is endogenously determined. Simply put, our evidence strongly points to the fact that money supply in Malaysia is credit-driven and demand determined.